An unusually stable solid state Ag|AgCl reference electrode for long term continuous measurements based on a crosslinked poly(vinyl acetate)/KCl composite. (1st February 2021) - Macedo, David S.; Vepsäläinen, Mikko; Acharya, Durga; Wood, Colin D.; Wen, Dingchen; Thomson, Liam; Peacock, Stephen; Rodopoulos, Theo; Hogan, Conor F.
Highlights: A solid-state reference electrode demonstrating a continuous working lifetime of 175 days. Polymer crosslinking significantly reduced rate of electrolyte leakage. Polymer crosslinking improved performance in strongly alkaline and acidic solutions. Stable reference potential over 1–10 pH range. Abstract: Electrochemical measurements are attractive for continuous or long-term monitoring of chemical species in a range of analytical applications including health, environmental and agricultural monitoring, as well as food analysis and industrial process control. A significant barrier to long-term electrochemical measurements in continuous online monitoring applications is the requirement for stable and durable reference electrodes. Most reference electrodes require regular maintenance in such situations to maintain the concentration of the internal electrolyte reservoir and prevent fouling of the electrode. Solid state reference electrodes (SSREs) are well suited to these long-term monitoring applications, but most only have their short-term performance reported or are designed for disposable applications. Additionally, polymer crosslinking has been demonstrated as an effective way to slow leakage of suspended solutes, improve chemical resistance, and control a polymer's physical properties; but application of this technique in SSRE materials is yet to be reported. This work describes the construction and performance of a novel SSRE with exceptional long-term stability, using an ethylene glycol dimethacrylate (EGDMA) crosslinked PVAc/KCl composite material. Open circuit potentiometry and electrochemical impedance spectroscopy were used to study the electrochemical performance. Conductivity measurements and micro X-ray fluorescence mapping were used to examine the effect of EGDMA crosslinking on electrolyte leakage and electrode lifetime. A SSRE with a 1% molar ratio of EGDMA/vinyl acetate proved to be exceptionally stable and provided a reliable reference potential for at least 175 days in a 1 M Na2 SO4 solution. PVAc/KCl composites without crosslinker were found to leak electrolyte ca . 30% faster than those with 1% EGDMA. EGDMA crosslinking also was shown to improve electrochemical performance and SSRE lifetime in both highly acidic and strongly alkaline solutions, suggesting a broad range of applications. Additionally, a 1% crosslinked SSRE demonstrated comparable performance to a commercial reference electrode in potentiometric and voltammetric measurements. The results demonstrate that crosslinked polymer-electrolyte composites provide a promising new approach for improving reference electrode performance in electrochemical measurements, particularly in continuous long-term online monitoring applications. Graphical abstract: Image, graphical abstract